A Molecularly Imprinted Polymer Based SPR Sensor for 2-Furaldehyde Determination in Oil Matrices - Maria Pesavento (MDPI AG, 2021)
Optical chemosensors with surface plasmon resonance (SPR) transduction are widely employed, even in complex environments, such as those outside the laboratory. In this context, not only the chemical nature but also the physical form of the receptor layer is particularly relevant. Synthetic receptors as molecularly imprinted polymers (MIPs) are well suited. This is demonstrated here in the case of an SPR sensor platform based on a multimode plastic optical fiber, which is very promising for on site application due to the low dimensions and low cost. A specific MIP was used as the receptor, with high affinity for the substance to be determined, 2-furaldehyde, in water. Here, a medium of high refractive index, i.e., vegetable oil, was considered because of the high interest for its determination in industrial diagnostics. The effects of the MIP layer thickness and the washing extent on the quality of the analytical signal were investigated. Better spectra were generated at the thinner MIP layer, while a lower detection limit is reached with extended washing.